Piperlongumine inhibits migration and proliferation of castration-resistant prostate cancer cells via triggering persistent DNA damage - Ding-fang Zhang; Zhi-chun Yang; Jian-qiang Chen; Xiang-xiang Jin; Yin-da Qiu; Xiao-jing Chen; Hong-yi Shi; Zhi-guo Liu; Min-shan Wang; Guang Liang; Xiao-hui Zheng (BMC, 2021)
Abstract Background Metastatic castration-resistant prostate cancer (CRPC) is the leading cause of death among men diagnosed with prostate cancer. Piperlongumine (PL) is a novel potential anticancer agent that has been demonstrated to exhibit anticancer efficacy against prostate cancer cells. However, the effects of PL on DNA damage and repair against CRPC have remained unclear. The aim of this study was to further explore the anticancer activity and mechanisms of action of PL against CRPC in terms of DNA damage and repair processes. Methods The effect of PL on CRPC was evaluated by MTT assay, long-term cell proliferation, reactive oxygen species assay, western blot assay, flow cytometry assay (annexin V/PI staining), β-gal staining assay and DAPI staining assay. The capacity of PL to inhibit the invasion and migration of CRPC cells was assessed by scratch-wound assay, cell adhesion assay, transwell assay and immunofluorescence (IF) assay. The effect of PL on DNA damage and repair was determined via IF assay and comet assay. Results The results showed that PL exhibited stronger anticancer activity against CRPC compared to that of taxol, cisplatin (DDP), doxorubicin (Dox), or 5-Fluorouracil (5-FU), with fewer side effects in normal cells. Importantly, PL treatment significantly decreased cell adhesion to the extracellular matrix and inhibited the migration of CRPC cells through affecting the expression and distribution of focal adhesion kinase (FAK), leading to concentration-dependent inhibition of CRPC cell proliferation and concomitantly increased cell death. Moreover, PL treatment triggered persistent DNA damage and provoked strong DNA damage responses in CRPC cells. Conclusion Collectively, our findings demonstrate that PL potently inhibited proliferation, migration, and invasion of CRPC cells and that these potent anticancer effects were potentially achieved via triggering persistent DNA damage in CRPC cells.